PENDIDIKAN KEAGAMAAN SOSIALIS-HUMANIS SEBAGAI BASIS MODERASI BERAGAMA - Herrio Tekdi Nainggolan; Trinovianto G.R. Hallatu; Ni Nyoman Rediani; Bernadetha Rizki Kaize (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
Education as an instrument of human civilization has a very central role and function in shaping patterns of human behavior both individually and in groups when interacting in society. This paper explores how socialist-humanist religious education becomes the basis of religious moderation for society in the midst of religious diversity and complexity. By using a qualitative research method and a literature review approach to study the subject matter, the answers to the problems in this paper are presented in a descriptive narrative form. The results of the study show that socialist-humanist religious education is able to awaken the religious community to interpret and understand not only the religion they adhere to but also other religions in relation to social and human relations. Socialist-humanist religious education makes it possible to interpret and understand religion broadly and deeply so that it does not belittle the substance of religion only in the realm of divinity. With such a meaning and understanding of religion, the essence of religious people, namely being tolerant and moderately religious, can be realized. Religion is not only understood in the theological-dogmatic realm, but religious messages are also understood in a socialist-humanist sense.